Polarizing plate for light emitting display device and light emitting display device including the same
The polarizing plate for organic light-emitting display devices addresses the challenge of achieving high peeling force and reliability by using a laminated structure with specific adhesive and liquid crystal retardation films, ensuring excellent performance under varying conditions.
Patent Information
- Application Number
- JP2022552527
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-06
- Filing Date
- 2021-02-10
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2041-02-10
AI Technical Summary
Existing polarizing plates for organic light-emitting display devices face challenges in achieving excellent peeling force against liquid crystal retardation films, while maintaining reliability and flexibility, especially under high temperature and humidity conditions.
A polarizing plate design that includes a polarizer with successively laminated adhesive layers and liquid crystal retardation films, where the second adhesive layer is formed directly on the first and second liquid crystal retardation films, and is composed of an epoxy and (meth)acrylate compound mixture, ensuring high peeling force and flexibility.
The proposed polarizing plate achieves excellent peeling force, reliability, and flexibility, minimizing the influence of liquid crystal retardation films on polarization and maintaining performance under high temperature and humidity conditions.
Smart Images

Figure 0007659570000011 
Figure 0007659570000012 
Figure 0007659570000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing plate for a light emitting display device and a light emitting display device including the same. [Background technology]
[0002] An OLED display is a self-luminous display device and does not require a separate polarizing plate as in an LCD device. However, by providing a polarizer and a polarizing plate having a retardation film having a predetermined range of retardation between the polarizer and an OLED panel, linearly polarized light incident from the polarizer is converted into circularly polarized light, thereby preventing reflection of external light and improving screen quality.
[0003] In recent years, by using a thin liquid crystal retardation film as a retardation film, the above-mentioned screen quality improvement effect and the effect of making the polarizing plate thinner can be obtained at the same time. Although not particularly limited, a 1 / 2 retardation liquid crystal film and a 1 / 4 retardation liquid crystal film are laminated and used as the retardation film. Therefore, an adhesive layer with high peel strength is required for both the 1 / 2 retardation liquid crystal film and the 1 / 4 retardation liquid crystal film. Meanwhile, in recent years, while foldable displays have been developed, polarizing plates applicable to foldable displays are also required for organic light-emitting display devices.
[0004] The background art of the present invention is described in, for example, Japanese Patent Publication No. 2014-032270. Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a polarizing plate which has excellent peeling strength with respect to a liquid crystal retardation film, and is excellent in reliability and flexibility.
[0006] Another object of the present invention is to provide a polarizing plate capable of minimizing an effect on polarized light passing through a first liquid crystal retardation film and a second liquid crystal retardation film. [Means for solving the problem]
[0007] One aspect of the present invention is a polarizing plate for a light-emitting display device.
[0008] 1. A polarizing plate for an emissive display device includes a polarizer, and a first adhesive layer, a first liquid crystal retardation film, a second adhesive layer, and a second liquid crystal retardation film, which are sequentially laminated on one surface of the polarizer, and the polarizing plate for an emissive display device has polarization degree changes (△PE1, △PE2) of the following Equation 1 and the following Equation 2 of about 0.7% or less, respectively:
[0009]
number
[0010] (In the above formula 1, the polarizing plate is cut to a length x width (3 cm x 3 cm, MD of polarizer x TD of polarizer), and the initial polarization degree measured for the test piece is P1 (unit: %). The polarization degree measured after leaving the test piece at a constant temperature of 85°C for 500 hours is called P2 (unit: %).
[0011]
number
[0012] (In the above formula 2, a polarizing plate is cut to a length x width (3 cm x 3 cm, MD of polarizer x TD of polarizer), and the initial polarization degree measured on the test piece is called P1 (unit: %), and the polarization degree measured after leaving the test piece at a constant temperature and humidity of 60°C and 95% relative humidity for 500 hours is called P3 (unit: %).) In 2.1, the second adhesive layer may be directly formed on the first liquid crystal retardation film and the second liquid crystal retardation film, respectively.
[0013] In 3.1-2, the second adhesive layer is formed of a composition including an epoxy-based compound and a (meth)acrylate-based compound, and the (meth)acrylate-based compound may include a hydrophobic (meth)acrylate-based compound.
[0014] In 4.3, the hydrophobic (meth)acrylate-based compound may include a (meth)acrylate having a linear or branched unsubstituted alkyl group having 6 to 20 carbon atoms, and a (meth)acrylate having an unsubstituted aromatic group.
[0015] In 5.4, the (meth)acrylate having a linear or branched unsubstituted alkyl group having 6 to 20 carbon atoms may include one or more of isodecyl (meth)acrylate and decyl (meth)acrylate.
[0016] In 6.1-5, the epoxy compound may include an alicyclic epoxy compound.
[0017] In 7.1-6, the epoxy compound may further include an aromatic group-containing glycidyl ether.
[0018] In 8.7, the aromatic group-containing glycidyl ether can include one or more of phenyl glycidyl ether and resorcinol diglycidyl ether.
[0019] In 9.1-8, the composition may not contain a (meth)acrylate compound having a hydrophilic group.
[0020] In 10.1-9, the (meth)acrylate compound may be included in an amount of about 25 parts by weight to about 65 parts by weight based on 100 parts by weight of the total of the epoxy compound and the (meth)acrylate compound.
[0021] In 11.1-10, the composition may further include a photocationic initiator and a photoradical initiator.
[0022] In 12.11, the composition may include about 35 parts by weight to about 90 parts by weight of the epoxy-based compound, about 10 parts by weight to about 65 parts by weight of the (meth)acrylate-based compound, about 1 part by weight to about 10 parts by weight of the photocationic initiator, and about 0.5 parts by weight to about 10 parts by weight of the photoradical initiator, per 100 parts by weight of the total of the epoxy-based compound and the (meth)acrylate-based compound.
[0023] In 13.1-12, the second adhesive layer may have a glass transition temperature of about 70°C to about 110°C.
[0024] In 14.1-13, the first adhesive layer is formed of a composition including an epoxy-based compound and a (meth)acrylate-based compound, and the (meth)acrylate-based compound may include a hydrophobic (meth)acrylate-based compound.
[0025] In 15.14, the composition may not contain a (meth)acrylate compound having a hydrophilic group.
[0026] In 16.1-15, the first adhesive layer may have a glass transition temperature of about 70°C to about 110°C.
[0027] In 17.1-16, the first liquid crystal retardation film and the second liquid crystal retardation film may be formed of a composition containing one or more of an alicyclic group-containing (meth)acrylic liquid crystal compound and an aromatic group-containing (meth)acrylic liquid crystal compound.
[0028] In 18.1-17, a protective layer may be further formed on the other surface of the polarizer.
[0029] Another aspect of the present invention is a light emitting display device.
[0030] 19. A light-emitting display device includes the polarizing plate for a light-emitting display device of the present invention.
[0031] In 20.19, the light-emitting display device may include a foldable light-emitting display device. Effect of the Invention
[0032] The present invention can provide a polarizing plate that has excellent peeling strength with respect to a liquid crystal retardation film, and is excellent in reliability and flexibility.
[0033] The present invention can provide a polarizing plate capable of minimizing the influence on polarized light passing through a first liquid crystal retardation film and a second liquid crystal retardation film. [Brief description of the drawings]
[0034] [Figure 1] 1 is a cross-sectional view of a polarizing plate for a light-emitting display device according to an embodiment of the present invention. [Diagram 2] FIG. 4 is a cross-sectional view of a polarizing plate for a light-emitting display device according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] [Best Mode for Carrying Out the Invention] The present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily carry out the present invention. The present invention may be embodied in various different forms and is not limited to the embodiments described herein. In the drawings, parts that are not related to the description are omitted in order to clearly explain the present invention, and the same reference numerals are used throughout the specification to refer to the same or similar components. In the drawings, the length, thickness, etc. of each component are shown for the purpose of explaining the present invention, and the present invention is not limited to the length, thickness, etc. described in the drawings.
[0036] In this specification, "upper" and "lower" are based on the drawings and are not necessarily fixed as upper and lower, but "upper" may change to "lower" and "lower" to "upper" depending on the viewing angle.
[0037] In this specification, the "in-plane retardation (Re)" can be expressed by the following formula A:
[0038]
number
[0039] (In the above formula A, nx and ny are the refractive indices in the slow axis and fast axis directions of the liquid crystal retardation film at a wavelength of 550 nm, respectively, and d is the thickness of the liquid crystal retardation film (unit: nm).)
[0040] In this specification, the term "light emitting element" includes an organic or organic / inorganic light emitting element, and may refer to an element including a light emitting material such as an LED (light emitting diode), an OLED (organic light emitting diode), a QLED (quantum dot light emitting diode), or a phosphor.
[0041] In this specification, when describing a numerical range, "X to Y" means X or more and Y or less (X≦and≦Y).
[0042] The inventors of the present invention have discovered that a polarizing plate for a light-emitting display device, in which a polarizer, a first adhesive layer, a first liquid crystal retardation film, a second adhesive layer, and a second liquid crystal retardation film are laminated in this order, The present invention has been completed by confirming that the peel strength of the second adhesive layer for each of the first liquid crystal retardation film and the second liquid crystal retardation film can be increased to increase the reliability of the polarizing plate at high temperature and / or high temperature and high humidity, while improving the flexibility of the polarizing plate and minimizing the effect of the liquid crystal retardation film on light reflection.
[0043] The present invention has been able to obtain the effects of the present invention by limiting the compositions of the first adhesive layer that bonds the polarizer and the first liquid crystal retardation film to each other, and the second adhesive layer that bonds the first liquid crystal retardation film and the second liquid crystal retardation film to each other, among several adhesive or pressure-sensitive adhesive layers that may be included in the polarizing plate for a light-emitting display device.
[0044] Hereinafter, a polarizing plate for a light-emitting display device (hereinafter, also referred to as a "polarizing plate") according to one embodiment of the present invention will be described with reference to FIG.
[0045] Referring to FIG. 1, the polarizing plate includes a polarizer 10, a first adhesive layer 50, a first liquid crystal retardation film 20, a second adhesive layer 30, and a second liquid crystal retardation film 40, which are laminated in this order on one surface of the polarizer 10.
[0046] 2nd adhesive layer The second adhesive layer 30 is formed directly on each of the first liquid crystal retardation film 20 and the second liquid crystal retardation film 40. The term "directly formed" means that no other adhesive layer, adhesive layer, or pressure-sensitive adhesive layer other than the second adhesive layer 30 is interposed between the first liquid crystal retardation film 20 and the second liquid crystal retardation film 40.
[0047] The second adhesive layer 30 has a high peel strength with respect to each of the first liquid crystal retardation film 20 and the second liquid crystal retardation film 40, and therefore prevents separation between the first liquid crystal retardation film and the second liquid crystal retardation film, thereby maintaining the polarizing plate and preventing separation or blisters from occurring under reliable conditions (especially high temperature / high humidity).
[0048] The peel strength of the second adhesive layer to the first liquid crystal retardation film and the peel strength of the second adhesive layer to the second liquid crystal retardation film may be about 100 gf / 25 mm or more, for example, about 100 gf / 25 mm to about 3,000 gf / 25 mm, respectively. In this range, the first liquid crystal retardation film and the second liquid crystal retardation film are not separated from each other under room temperature conditions, and the polarizing plate can be maintained.
[0049] The second adhesive layer 30 can enhance the flexibility of the polarizer by preventing wrinkles and cracks from occurring in the first liquid crystal retardation film and the second liquid crystal retardation film during the evaluation of the flexibility of the polarizer described below in detail, and thus can improve the screen quality when the polarizer is used in a foldable light emitting display device.
[0050] The "flexibility evaluation" was performed on the polarizing plate of the present invention (a polarizing plate laminated in the order of a polarizer protective layer, a polarizer, a first adhesive layer, a first liquid crystal retardation film, a second adhesive layer, and a second liquid crystal retardation film) based on IEC-62715. Specifically, a polyethylene terephthalate (PET) film having a thickness of 80 μm was adhered to one surface of the polarizing plate of the present invention with an acrylic adhesive, and a PET film having a thickness of 80 μm was adhered to the other surface of the polarizing plate with an acrylic adhesive, and a test piece was prepared by cutting the test piece into a length x width (6 cm x 4 cm, length: MD of polarizer, width: TD of polarizer). The test piece was mounted on a bending tester so that the PET film closest to the polarizer was on the inside when bent, and was bent at 25° C. with a bending radius of 5 mm, a bending repetition rate of 30 times / min, and a bending angle of 180°, and the minimum number of bending times at which wrinkles or cracks were generated in the first liquid crystal retardation film and / or the second liquid crystal retardation film was evaluated. When the minimum number of flexions is 100,000 or more, the display quality can be improved even when the polarizing plate is used in a foldable light-emitting display device.
[0051] The second adhesive layer 30 is formed between the first liquid crystal retardation film 20 and the second liquid crystal retardation film 40, and can minimize the influence on light in the process of changing linearly polarized light passing through the polarizer 10 into circularly polarized light when the linearly polarized light passes through the first liquid crystal retardation film 20, the second adhesive layer 30, and the second liquid crystal retardation film 40 in sequence. This can improve the circular polarization effect by the first liquid crystal retardation film and the second liquid crystal retardation film.
[0052] The second adhesive layer 30 can improve the reliability when the polarizing plate is left at high temperature and / or high temperature and high humidity. The first liquid crystal retardation film adhered to one side of the polarizer is thin and cannot sufficiently reduce the change in the polarization degree when the polarizing plate is left at high temperature and / or high temperature and high humidity. On the other hand, the second adhesive layer is formed on one side of the first liquid crystal retardation film, i.e., on the side of the first liquid crystal retardation film to which the polarizer is not adhered, and can reduce the change in the polarization degree and improve the reliability.
[0053] For example, the polarizing plate of the present invention may have a polarization degree change amount (ΔPE1, ΔPE2) according to the following formula 1 and the following formula 2 of about 0.7% or less, for example, about 0% to about 0.7%. For example, the polarizing plate of the present invention may have a polarization degree change amount (ΔPE1, ΔPE2) according to the following formula 1 and the following formula 2 of about 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, or 0.7%:
[0054]
number
[0055] (In the above formula 1, the polarizing plate is cut to a length x width (3 cm x 3 cm, MD of polarizer x TD of polarizer), and the initial polarization degree measured for the test piece is P1 (unit: %). The polarization degree measured after leaving the test piece at a constant temperature of 85°C for 500 hours is called P2 (unit: %).
[0056]
number
[0057] (In the above formula 2, the polarizing plate is cut to a length x width (3 cm x 3 cm, MD of polarizer x TD of polarizer), and the initial polarization degree measured for the test piece is P1 (unit: %). The polarization degree measured after leaving the test piece at a constant temperature and humidity of 60°C and 95% relative humidity for 500 hours is called P3 (unit: %).
[0058] The second adhesive layer 30 may have a glass transition temperature of about 70° C. to about 110° C. In this range, the peel strength between the first liquid crystal retardation film and the second liquid crystal retardation film may be excellent, and the flexibility and reliability may be excellent. Preferably, the glass transition temperature of the second adhesive layer 30 may be greater than about 70° C. and less than about 110° C., more preferably about 85° C. to about 100° C.
[0059] The second adhesive layer 30 is formed of an adhesive composition including an epoxy-based compound and a hydrophobic (meth)acrylate-based compound, which will be described in detail below.
[0060] Each component of the adhesive composition will now be described in detail.
[0061] Epoxy Compounds The epoxy-based compound includes an alicyclic epoxy-based compound. The "alicyclic epoxy-based compound" may mean a compound having an epoxidized alicyclic group. For example, the alicyclic epoxy-based compound may include, but is not limited to, one or more of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 3,4-epoxy-6-methylcyclohexylmethyl-3',4'-epoxy-6'-methylcyclohexanecarboxylate, bis(3,4-epoxy-6-methylcyclohexyl)adipate, bicyclohexyl diepoxide (3,4,3',4'-diepoxy-bicyclohexane), and 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate modified epsilon-caprolactone as a bifunctional alicyclic epoxy-based compound.
[0062] The alicyclic epoxy compound may be included in an amount of about 40 parts by weight to about 90 parts by weight, specifically about 50 parts by weight to about 90 parts by weight, or about 50 parts by weight to about 80 parts by weight, out of a total of 100 parts by weight of the epoxy compound and the (meth)acrylate compound. In this range, the adhesive strength between the liquid crystal retardation film is excellent, there is no decrease in wettability due to an increase in the viscosity of the composition, and there is no brittle characteristic of the adhesive layer due to an excessive increase in modulus, so that the effect of having no problem in the crack resistance and cutting property of the polarizing plate can be realized. For example, the alicyclic epoxy compound is about 40 parts by weight, 41 parts by weight, 42 parts by weight, 43 parts by weight, 44 parts by weight, 45 parts by weight, 46 parts by weight, 47 parts by weight, 48 parts by weight, 49 parts by weight, 50 parts by weight, 51 parts by weight, 52 parts by weight, 53 parts by weight, 54 parts by weight, 55 parts by weight, 56 parts by weight, 57 parts by weight, 58 parts by weight, 59 parts by weight, 60 parts by weight, 61 parts by weight, or the like, based on 100 parts by weight of the total of the epoxy compound and the (meth)acrylate compound.
[0043] In some embodiments, the composition may be present in an amount of 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, 86 parts, 87 parts, 88 parts, 89 parts, or 90 parts by weight.
[0063] The epoxy-based compound may further include an aromatic group-containing glycidyl ether.
[0064] The aromatic group-containing glycidyl ether is contained in the epoxy compound, so that the post-curing effect due to the dark reaction and the improvement of the adhesion with the liquid crystal retardation film can be further realized. In the present invention, the alicyclic epoxy compound and the aromatic group-containing glycidyl ether are contained at the same time, so that the effects of the present invention can be further realized.
[0065] The aromatic group-containing glycidyl ether can include a compound having one or more glycidyl ether groups. The "glycidyl ether group" can refer to a moiety of the following formula 1:
[0066] [ka]
[0067] (In the above Chemical Formula 1, * is a linking site.)
[0068] The aromatic group-containing glycidyl ether can be a monofunctional glycidyl ether and contain an aromatic group and one glycidyl ether group. For example, the monofunctional glycidyl ether can include, but is not limited to, phenyl glycidyl ether, etc.
[0069] The aromatic group-containing glycidyl ether can be a difunctional diglycidyl ether containing an aromatic group and two glycidyl ether groups. For example, the difunctional diglycidyl ether can include one or more of resorcinol diglycidyl ether and 4,4'-(1-methylethylidene)biphenol polymer with (chloromethyl)oxirane.
[0070] In one embodiment, the aromatic group-containing glycidyl ether may include only monofunctional glycidyl ethers.
[0071] In other embodiments, the aromatic group-containing glycidyl ether may include only difunctional glycidyl ethers.
[0072] In yet another embodiment, the aromatic group-containing glycidyl ether can include a mixture of monofunctional and difunctional glycidyl ethers, for example, the aromatic group-containing glycidyl ether can include one or more of phenyl glycidyl ether and resorcinol diglycidyl ether.
[0073] The aromatic group-containing glycidyl ether may be included in an amount of about 0 to about 10 parts by weight, specifically about 0.1 to about 10 parts by weight, more specifically about 1 to about 10 parts by weight, out of a total of 100 parts by weight of the epoxy compound and the (meth)acrylate compound. In this range, the effect of not slowing down the initial curing speed, not causing a problem of initial adhesive strength reduction, and not reducing reliability and peel strength at high temperature and high humidity can be realized. For example, the aromatic group-containing glycidyl ether may be included in an amount of about 0 parts by weight, 0.1 parts by weight, 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, 0.8 parts by weight, 0.9 parts by weight, 1 parts by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, or 10 parts by weight.
[0074] The epoxy compound may be included in an amount of about 35 parts by weight to about 90 parts by weight, specifically about 35 parts by weight to about 85 parts by weight, or about 35 parts by weight to about 75 parts by weight, out of a total of 100 parts by weight of the epoxy compound and the (meth)acrylate compound. In this range, an excellent crack resistance improvement effect can be realized due to an increase in the glass transition temperature of the adhesive layer. For example, the epoxy compound may be included in an amount of about 35 parts by weight, 36 parts by weight, 37 parts by weight, 38 parts by weight, 39 parts by weight, 40 parts by weight, 41 parts by weight, 42 parts by weight, 43 parts by weight, 44 parts by weight, 45 parts by weight, 46 parts by weight, 47 parts by weight, 48 parts by weight, 49 parts by weight, 50 parts by weight, 51 parts by weight, 52 parts by weight, 53 parts by weight, 54 parts by weight, 55 parts by weight, 56 parts by weight, 57 parts by weight, 58 parts by weight, 59 parts by weight, 60 parts by weight, 61 parts by weight, 62 parts by weight, or 63 parts by weight.
[0043] The composition may be comprised in an amount of 63 parts by weight, 64 parts by weight, 65 parts by weight, 66 parts by weight, 67 parts by weight, 68 parts by weight, 69 parts by weight, 70 parts by weight, 71 parts by weight, 72 parts by weight, 73 parts by weight, 74 parts by weight, 75 parts by weight, 76 parts by weight, 77 parts by weight, 78 parts by weight, 79 parts by weight, 80 parts by weight, 81 parts by weight, 82 parts by weight, 83 parts by weight, 84 parts by weight, 85 parts by weight, 86 parts by weight, 87 parts by weight, 88 parts by weight, 89 parts by weight or 90 parts by weight.
[0075] (Meth)acrylate compounds The (meth)acrylate compound undergoes polymerization by a photoradical initiator initiated by light energy, and can stably react with light energy without being inhibited by moisture.
[0076] The composition of the present invention contains, as a (meth)acrylate-based compound, a (meth)acrylate-based compound having absolutely no hydrophilic groups including hydroxyl groups, carboxylic acid groups, etc. In this specification, a (meth)acrylate-based compound having absolutely no hydrophilic groups including hydroxyl groups, carboxylic acid groups, etc. is named a "hydrophobic (meth)acrylate-based compound."
[0077] The composition of the present invention contains a hydrophobic (meth)acrylate compound as a (meth)acrylate compound, thereby improving the reliability of the polarizing plate, particularly the reliability of the polarizing plate after it has been left at high temperature and high humidity for a long period of time.
[0078] In one embodiment, the composition does not include a (meth)acrylate compound having a hydrophilic group.
[0079] The hydrophobic (meth)acrylate-based compound includes (meth)acrylates having a straight-chain or branched-chain unsubstituted alkyl group having 6 to 20 carbon atoms and (meth)acrylates having an unsubstituted aromatic group. If any one of them is missing, the glass transition temperature of the adhesive layer exceeds 110°C or the glass transition temperature of the second adhesive layer of the present invention is not satisfied, resulting in poor flexibility, low peel strength to the liquid crystal retardation film, and poor reliability. By including both (meth)acrylates having a straight-chain or branched-chain unsubstituted alkyl group having 6 to 20 carbon atoms and (meth)acrylates having an aromatic group, the effects of the present invention can be well realized. Here, the "carbon number" of the alkyl group is a value excluding the number of carbons contained in the (meth)acrylate group.
[0080] The (meth)acrylate having a straight or branched unsubstituted alkyl group having 6 to 20 carbon atoms may include one or more of hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate. Preferably, the (meth)acrylate has a branched unsubstituted alkyl group having 6 to 20 carbon atoms, more preferably, the (meth)acrylate has a branched unsubstituted alkyl group having 8 to 12 carbon atoms. Most preferably, the (meth)acrylate has one or more of isodecyl (meth)acrylate and decyl (meth)acrylate.
[0081] The (meth)acrylate having a straight or branched unsubstituted C6 to C20 alkyl group may be included in an amount of about 1 to about 30 parts by weight, for example, about 5 to about 20 parts by weight, per 100 parts by weight of the epoxy compound and the (meth)acrylate compound in total. Within this range, the adhesive layer may have excellent peel strength and the polarizing plate may have excellent reliability under high temperature and high humidity. For example, (meth)acrylates having a straight or branched unsubstituted alkyl group having 6 to 20 carbon atoms may be included in an amount of about 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight, 21 parts by weight, 22 parts by weight, 23 parts by weight, 24 parts by weight, 25 parts by weight, 26 parts by weight, 27 parts by weight, 28 parts by weight, 29 parts by weight, or 30 parts by weight.
[0082] The (meth)acrylate having an aromatic group can include, as a monofunctional or polyfunctional (meth)acrylate, for example, a (meth)acrylate having an aryloxy group (e.g., a phenoxy group) having 6 to 20 carbon atoms, an alkyl group having 1 to 5 carbon atoms, an alkylene group having 1 to 5 carbon atoms, or an alkylene oxide group having 1 to 5 carbon atoms. Preferably, the aromatic group-containing (meth)acrylate can include phenol (ethoxylated) (meth)acrylate.
[0083] The aromatic group-containing (meth)acrylate may be included in an amount of about 1 to about 20 parts by weight, for example, about 5 to about 20 parts by weight, out of a total of 100 parts by weight of the epoxy compound and the (meth)acrylate compound. In this range, the glass transition temperature of the adhesive layer of the present invention can be reached and the initial adhesive strength can be improved. For example, the aromatic group-containing (meth)acrylate may be included in an amount of about 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, or 20 parts by weight.
[0084] The (meth)acrylate compound, preferably the hydrophobic (meth)acrylate compound, may be included in an amount of about 10 parts by weight to about 65 parts by weight, for example, about 15 parts by weight to about 65 parts by weight, about 25 parts by weight to about 65 parts by weight, based on 100 parts by weight of the total of the epoxy compound and the (meth)acrylate compound. In this range, when the adhesive composition having excellent adhesive strength of the adhesive layer is cured, the adhesion to the surface of the liquid crystal retardation film may not be reduced due to a decrease in contraction force. For example, the (meth)acrylate-based compound, preferably the hydrophobic (meth)acrylate-based compound, is about 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight, 21 parts by weight, 22 parts by weight, 23 parts by weight, 24 parts by weight, 25 parts by weight, 26 parts by weight, 27 parts by weight, 28 parts by weight, 29 parts by weight, 30 parts by weight, 31 parts by weight, 32 parts by weight, 33 parts by weight, 34 parts by weight, It may be included in an amount of 35 parts by weight, 36 parts by weight, 37 parts by weight, 38 parts by weight, 39 parts by weight, 40 parts by weight, 41 parts by weight, 42 parts by weight, 43 parts by weight, 44 parts by weight, 45 parts by weight, 46 parts by weight, 47 parts by weight, 48 parts by weight, 49 parts by weight, 50 parts by weight, 51 parts by weight, 52 parts by weight, 53 parts by weight, 54 parts by weight, 55 parts by weight, 56 parts by weight, 57 parts by weight, 58 parts by weight, 59 parts by weight, 60 parts by weight, 61 parts by weight, 62 parts by weight, 63 parts by weight, 64 parts by weight or 65 parts by weight.
[0085] Initiator The initiator may include a mixture of photocationic and photoradical initiators.
[0086] The photocationic initiator can include any conventional photocationic initiator capable of carrying out a photocurable reaction.
[0087] The photocationic initiator may include an onium salt of a cation and an anion, which are onium ions. Specific examples of the onium ion include diaryliodonium such as diphenyliodonium, 4-methoxydiphenyliodonium, bis(4-methylphenyl)iodonium, bis(4-tert-butylphenyl)iodonium, bis(dodecylphenyl)iodonium, (4-methylphenyl)[(4-(2-methylpropyl)phenyl)iodonium, triarylsulfonium such as triphenylsulfonium, diphenyl-4-thiophenoxyphenylsulfonium, diphenyl-4(phenylthio)phenylsulfonium, bis[4-(diphenylsulfonio)-phenyl]sulfide, bis[4-(di(4-(2-hydroxyethyl)phenyl)sulfonio)-phenyl]sulfide, and 5-2,4-(cyclopentadienyl)[1,2,3,4,5,6-η]-(methylethyl)-benzene]-iron(1+). A specific example of an anion is tetrafluoroborate (BF4 - ), hexafluorophosphate (PF6 - ), hexafluoroantimonate (SbF6 - ), hexafluoroarsenate (AsF6 - ), hexachloroantimonate (SbCl6 - ) etc.
[0088] The photocationic initiator may be included in an amount of about 1 part by weight to about 10 parts by weight, for example, about 2 parts by weight to about 10 parts by weight, based on 100 parts by weight of the total of the epoxy compound and the (meth)acrylate compound. In this range, problems such as a decrease in peel strength and bleeding out of the photocationic initiator due to the adhesive layer composition not being sufficiently cured may not occur. For example, the photocationic initiator may be included in an amount of about 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, or 10 parts by weight.
[0089] The photoradical initiator generates a small amount of radicals by irradiation with light, and catalyzes the curing reaction. The photoradical initiator may include a phenyl ketone type, a phosphorus type, a triazine type, an acetophenone type, a benzophenone type, a thioxanthone type, a benzoin type, an oxime type, or a mixture thereof. In a specific example, a phenyl ketone type or a mixture thereof may be included as the photoradical initiator.
[0090] The photoradical initiator may be included in an amount of 0.5 to 10 parts by weight, for example, 0.5 to 6 parts by weight, based on 100 parts by weight of the total of the epoxy compound and the (meth)acrylate compound. In this range, the (meth)acrylate compound may be sufficiently cured under the light intensity conditions of the process, and the reactivity of the photocationic initiator may be improved. For example, the photoradical initiator may be included in an amount of about 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, 0.8 parts by weight, 0.9 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, or 10 parts by weight.
[0091] The composition for the second adhesive layer may be prepared by mixing the epoxy compound, the (meth)acrylate compound, the photocationic initiator, and the photoradical initiator. The composition for the second adhesive layer may be a solvent-free type without a solvent, or may further contain a solvent to improve the applicability (coating property).
[0092] The composition for the second adhesive layer may further contain an antioxidant, an ultraviolet absorber, an ionic conductive agent, a conductivity-imparting additive such as conductive metal oxide fine particles, an additive for imparting light diffusion properties, a viscosity adjuster, etc., within a range that does not impair the effects of the present invention.
[0093] The composition for the second adhesive layer has a UVA wavelength of about 50 mJ / cm 2 ~400mJ / cm 2 Preferably, about 60 mJ / cm 2 ~300mJ / cm 2 The second adhesive layer can be formed by being photocured by irradiating the adhesive with a light amount of 1000 nm.
[0094] The second adhesive layer 30 may have a thickness of about 0.1 μm to about 30 μm, for example, about 1 μm to about 10 μm. In this range, the second adhesive layer 30 can secure a peeling force for each of the first liquid crystal retardation film and the second liquid crystal retardation film by securing an appropriate thickness, and can be used for a polarizing plate.
[0095] First liquid crystal retardation film and second liquid crystal retardation film The first liquid crystal retardation film 20 and the second liquid crystal retardation film 40 convert the linearly polarized light emitted after the external light passes through the polarizer into circularly polarized light, thereby preventing reflection of the external light and improving the screen quality.
[0096] In one specific example, the first liquid crystal retardation film may have Re of about 100 nm to about 220 nm, specifically about 100 nm to about 180 nm at a wavelength of 550 nm, for example, a λ / 4 retardation film, and the second liquid crystal retardation film may have Re of about 225 nm to about 350 nm, specifically about 225 nm to about 300 nm at a wavelength of 550 nm, for example, a λ / 2 retardation film.
[0097] In another specific example, the first liquid crystal retardation film may have Re of about 225 nm to about 350 nm, specifically about 225 nm to about 300 nm at a wavelength of 550 nm, for example, a λ / 2 retardation film, and the second liquid crystal retardation film may have Re of about 100 nm to about 220 nm, specifically about 100 nm to about 180 nm at a wavelength of 550 nm, for example, a λ / 4 retardation film.
[0098] The first liquid crystal retardation film and the second liquid crystal retardation film may have the same or different thicknesses. For example, the first liquid crystal retardation film and the second liquid crystal retardation film may have a thickness of about 0.1 μm to about 30 μm, for example, about 1 μm to about 10 μm. In this range, the polarizing plate can be thinned to realize a desired retardation.
[0099] In one embodiment, the first liquid crystal retardation film and the second liquid crystal retardation film may each be a single-layer liquid crystal retardation layer. When the first liquid crystal retardation film and the second liquid crystal retardation film are each a liquid crystal retardation layer, the first liquid crystal retardation film and the second liquid crystal retardation film are each composed of a single liquid crystal retardation layer, which has the effect of making the polarizing plate thinner.
[0100] The liquid crystal retardation layer may be formed of a composition containing at least one of an alicyclic group-containing (meth)acrylic liquid crystal compound and an aromatic group-containing (meth)acrylic liquid crystal compound. The liquid crystal retardation layer may further contain additives such as a leveling agent, a polymerization initiator, an alignment aid, a heat stabilizer, a lubricant, a plasticizer, and an antistatic agent.
[0101] In another embodiment, the first liquid crystal retardation film and the second liquid crystal retardation film may each include a substrate film and a liquid crystal retardation layer formed on the substrate film. The first liquid crystal retardation film and the second liquid crystal retardation film may be formed by coating a composition capable of forming a liquid crystal retardation layer on the substrate film and curing the composition.
[0102] Polarizer The polarizer 10 is formed on a first liquid crystal retardation film and can polarize external or internal light. When the first liquid crystal retardation film is a liquid crystal retardation layer, the first liquid crystal retardation film can be directly formed on the polarizer by coating the polarizer with a composition for forming a liquid crystal retardation layer and curing the composition.
[0103] The polarizer 10 may include a polyvinyl alcohol-based polarizer obtained by dyeing a polyvinyl alcohol-based film with iodine or the like. For example, a polyvinyl alcohol-based polarizer is manufactured by dyeing a polyvinyl alcohol film with iodine or a heterochromatic dye and stretching the film in a certain direction. Specifically, the polarizer 10 is manufactured through a swelling process, a dyeing step, and a stretching step. The method of performing each step is generally known to those skilled in the art. The polarizer 10 may have a thickness of about 1 μm to about 50 μm. The polarizer 10 within the above range can be used in a light-emitting display device.
[0104] 1st adhesive layer The first adhesive layer 50 is formed between the polarizer 10 and the first liquid crystal retardation film 20, and can adhere the polarizer and the first liquid crystal retardation film. In this case, the first adhesive layer may be formed of the adhesive composition for the second adhesive layer described above.
[0105] The first adhesive layer 50 may have a thickness of about 0.1 μm to about 30 μm, for example, about 1 μm to about 10 μm. Within this range, the first adhesive layer 50 can be used in a light emitting display device.
[0106] The first adhesive layer 50 may have the same or different glass transition temperature as the second adhesive layer. In one embodiment, the first adhesive layer 50 may have a glass transition temperature of about 70°C to about 110°C. In this range, the peel strength between the first liquid crystal retardation film and the polarizer may be excellent, and the flexibility and reliability may be excellent. Preferably, the glass transition temperature of the first adhesive layer 50 may be greater than about 70°C and less than about 100°C, more preferably about 85°C to about 100°C.
[0107] Although not shown in FIG. 1, an adhesive film may be further formed on the lower surface of the second liquid crystal retardation film, i.e., the surface of the second liquid crystal retardation film on which the adhesive layer is not formed, so that the polarizer for the light emitting display device can be adhered to the light emitting element (e.g., an organic light emitting element panel).
[0108] 1, the polarizing plate includes a first adhesive layer. However, when the first liquid crystal retardation film is a liquid crystal retardation layer, the case where the first liquid crystal retardation film is directly formed on the polarizer without using the first adhesive layer may also be included in the scope of the present invention.
[0109] A polarizing plate according to another embodiment of the present invention will now be described with reference to FIG.
[0110] 2, the polarizing plate may include a polarizer 10, a protective layer 60 formed on an upper surface of the polarizer 10, a first adhesive layer 50 sequentially formed on a lower surface of the polarizer 10, a first liquid crystal retardation film 20, a second adhesive layer 30, and a second liquid crystal retardation film 40. It is substantially the same as the polarizing plate of FIG. 1, except that a protective layer 60 is further formed on the upper surface of the polarizer 10.
[0111] The protective layer 60 may be formed on the upper surface of the polarizer to support the polarizer. In addition, since the protective layer is formed on the upper surface of the polarizer, when the first liquid crystal retardation film is formed on the lower surface of the polarizer, the first liquid crystal retardation film may be directly formed on the polarizer without using a first adhesive layer. The protective layer may include at least one of an optically transparent protective film and a protective coating layer.
[0112] When the protective layer is a protective film type, it may include a protective film formed of an optically transparent resin. The protective film may be formed by melting and extruding the resin. If necessary, a stretching process may be further added. The resin may include one or more of cellulose ester-based resins including triacetyl cellulose, cyclic polyolefin-based resins including cyclic olefin polymer (COP), polycarbonate-based resins, polyester-based resins including polyethylene terephthalate (PET), polyethersulfone-based resins, polysulfone-based resins, polyamide-based resins, polyimide-based resins, non-cyclic polyolefin-based resins, polyacrylate-based resins including polymethyl methacrylate resin, polyvinyl alcohol-based resins, polyvinyl chloride-based resins, and polyvinylidene chloride-based resins. Preferably, the protective film may be a film formed of a cyclic polyolefin-based resin including a cyclic polyolefin.
[0113] When the protective layer is a protective coating layer type, it is possible to improve adhesion to the polarizer, transparency, mechanical strength, thermal stability, moisture blocking property, and durability. In one specific example, the protective coating layer for the protective layer may be formed of an active energy ray curable resin composition including an active energy ray curable compound and a polymerization initiator.
[0114] The active energy ray curable compound may include one or more of a cationic polymerizable curable compound, a radical polymerizable curable compound, a urethane resin, and a silicon resin. The cationic polymerizable curable compound may be an epoxy-based compound having at least one epoxy group in the molecule, or an oxetane-based compound having at least one oxetane ring in the molecule. The radical polymerizable curable compound may be a (meth)acrylic-based compound having at least one (meth)acryloyloxy group in the molecule.
[0115] The thickness of the protective layer 60 may be about 5 μm to about 200 μm, specifically about 30 μm to about 120 μm, about 30 μm to about 100 μm in the case of a protective film type, and about 5 μm to about 50 μm in the case of a protective coating layer type. The protective layer 60 in this range can be used in a light emitting display device.
[0116] Although not shown in FIG. 2, a functional coating layer, such as a hard coating layer, an anti-fingerprint layer, an anti-reflection layer, etc., may be further formed on the upper surface of the protective layer 60.
[0117] 2, when the protective layer 60 is a protective film type, a third adhesive layer may be further formed between the protective layer and the polarizer. The third adhesive layer may be formed of a typical adhesive for polarizing plates, for example, a water-based adhesive containing a polyvinyl alcohol-based resin as an adhesive resin, a photocurable adhesive, and a decompression adhesive.
[0118] A polarizing plate according to still another embodiment of the present invention will now be described.
[0119] The polarizing plate of this embodiment is substantially the same as the polarizing plate of FIG. 1, except that at least one of the first adhesive layer 50 and the second adhesive layer 30 in the polarizing plate of FIG. 1 is formed from a composition further including a silane coupling agent in addition to the above-mentioned epoxy-based compound, (meth)acrylate-based compound, and initiator.
[0120] By forming at least one of the first adhesive layer 50 and the second adhesive layer 30 from a composition further containing a silane coupling agent, the reliability of the polarizing plate at high temperatures and / or high temperature and humidity can be further improved.
[0121] Silane coupling agents are siloxane groups (- * Si(OR 1 ) n (R 2 ) 3-n where n is an integer from 1 to 3, and R 1 is an alkyl group having 1 to 5 carbon atoms; R 2is a hydroxyl group, a halogen, or an alkyl group having 1 to 4 carbon atoms.) may be included as a typical compound known to those skilled in the art. In one specific example, the silane coupling agent may include one or more of an epoxy group-containing silane coupling agent such as 3-glycidoxypropyltrimethoxysilane or glycidoxypropylmethyldimethoxysilane; an unsaturated group-containing silane coupling agent such as vinyltrimethoxysilane; and a mercapto group-containing silane coupling agent such as mercaptopropyltrimethoxysilane.
[0122] The silane coupling agent may be included in an amount of about 0.01 to about 10 parts by weight, for example, about 0.1 to about 5 parts by weight, based on 100 parts by weight of the epoxy compound and the (meth)acrylate compound in total. In this range, the high temperature and high humidity reliability of the polarizing plate may be further improved. For example, the silane coupling agent may be included in an amount of about 0.01 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, 0.8 parts by weight, 0.9 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, or 10 parts by weight.
[0123] An emissive display device according to an embodiment of the present invention includes a polarizer for an emissive display device according to the present invention. For example, the emissive display device may include, but is not limited to, an organic light emitting display device. The polarizer for an emissive display device according to the present invention may be used in a non-foldable emissive display device, but may have excellent flexibility even when used in a foldable emissive display device.
[0124] [Mode for carrying out the invention] The present invention will be described in more detail with reference to the following preferred embodiments, however, the present invention is not limited to the following embodiments.
[0125] Example 1 A polyvinyl alcohol film (saponification degree: 99.5%, polymerization degree: 2000, thickness: 60 μm) was immersed in a 0.3% iodine aqueous solution for dyeing, and then stretched in the MD (machine direction) at a stretch ratio of 5.0. The stretched polyvinyl alcohol film was immersed in a 3% boric acid aqueous solution and a 2% potassium iodide aqueous solution for hue correction, and dried at 50°C for 4 minutes to produce a polarizer (thickness: 23 μm).
[0126] The first liquid crystal retardation film used was a liquid crystal coated retardation film (FUJIFILM Corporation, QL AA 328, containing a cyclic (aromatic group) acrylate-based liquid crystal retardation layer. Re at a wavelength of 550 nm: approximately 234 nm). Both sides of the liquid crystal coated retardation film were irradiated with 250 mJ / cm 2 It was corona treated.
[0127] A liquid crystal-coated retardation film (FUJIFILM Corporation, QA AB 318, containing a cyclic (aromatic group) acrylate-based liquid crystal retardation layer. Re at a wavelength of 550 nm: approximately 116 nm) was used as the second liquid crystal retardation film. Both sides of the liquid crystal-coated retardation film were irradiated with 250 mJ / cm 2 It was corona treated.
[0128] (1) Manufacture of primary polarizing plates A primary polarizing plate was prepared at 22°C to 25°C and a relative humidity of 20% to 60%, laminated in the following order: protective layer-composition for adhesive layer (third adhesive layer)-polarizer-composition for adhesive layer (first adhesive layer)-unsaponified triacetyl cellulose (TAC) film.
[0129] A cycloolefin polymer (COP) resin film (thickness: 30 μm, transparent protective film) was used as the protective layer. One side of the cycloolefin resin film was irradiated with 250 mJ / cm 2 It was corona treated.
[0130] The third adhesive layer was formed from a composition containing a polyvinyl alcohol-based water-based adhesive containing 100 parts by weight of water, 3 parts by weight of a polyvinyl alcohol-based resin (Z320, Nippon Synthetic Chemical Industry Co., Ltd.), and 3 parts by weight of glyoxal (TCL Corporation). The composition was applied to one side of the protective layer, which was then aligned with a polarizer, and then heat-cured in a 50°C drying oven for 1 minute and in an 85°C drying oven for 2 minutes to produce the third adhesive layer.
[0131] The first adhesive layer was prepared by coating a composition for an adhesive layer, which was a mixture of an epoxy compound, a (meth)acrylate compound, and an initiator according to Table 1 below, on one side of a polarizer, and laminating an unsaponified triacetyl cellulose (TAC) film.
[0132] (2) Manufacturing a laminate of the first liquid crystal retardation film, the second adhesive layer, and the second liquid crystal retardation film A laminate of the first liquid crystal retardation film-the second adhesive layer-the second liquid crystal retardation film was produced at 22° C. to 25° C. and a relative humidity of 20% to 60%.
[0133] The laminate was manufactured by coating a composition for a second adhesive layer, which was a mixture of an epoxy compound, a (meth)acrylate compound, an initiator, etc., on one side of a first liquid crystal retardation film, laminating the second liquid crystal retardation film, and exposing the first liquid crystal retardation film side, as shown in Table 1 below.
[0134] (3) Manufacture of polarizing plates The polarizing plates were prepared at 22° C. to 25° C. and a relative humidity of 20% to 60%.
[0135] After separating and removing the unsaponified TAC film from the primary polarizing plate produced in (1), the first liquid crystal retardation film-second adhesive layer-second liquid crystal retardation film laminate was placed together so that the first adhesive layer and the first liquid crystal retardation film were in contact with each other, and the second liquid crystal retardation film side was exposed to light using a metal halide lamp (LICHTZEN). A polarizing plate was produced in which the protective layer, the third adhesive layer (thickness: 0.1 μm, PVA-based water-based adhesive layer), the polarizer, the first adhesive layer (thickness: 3 μm, UV-curable adhesive layer of the present invention), the first liquid crystal retardation film (Re: about 234 nm), the second adhesive layer (thickness: 3 μm, UV-curable adhesive layer of the present invention), and the second liquid crystal retardation film (Re: about 116 nm) were laminated in this order.
[0136] Meanwhile, in order to measure the peel strength, a light-shielding part was attached to a part of the lower surface of the second liquid crystal retardation film, and then ultraviolet light was irradiated.
[0137] Examples 2 to 6 A polarizing plate was prepared in the same manner as in Example 1, except that the components and / or contents of the first adhesive layer composition and the second adhesive layer composition were changed as shown in Table 1 below.
[0138] Comparative Examples 1 to 4 A polarizing plate was prepared in the same manner as in Example 1, except that the components and / or contents of the first adhesive layer composition and the second adhesive layer composition were changed as shown in Table 1 below.
[0139] The components and contents (unit: parts by weight) of the first adhesive layer composition and the second adhesive layer composition of the examples and comparative examples are shown in Table 1 below. In Table 1 below, each component is shown as the solid content excluding the solvent. In Table 1 below, "-" means that the corresponding component is not included.
[0140] Glass transition temperature (Tg) of the second adhesive layer (or the first adhesive layer) (unit: °C): The composition for the second adhesive layer was coated to a predetermined thickness on a processing film (PET film) and cured by passing ultraviolet light through it to prepare a test specimen having a second adhesive layer with a thickness of 5 μm to 10 μm. The prepared test specimen was measured for tan δ using a dynamic mechanical analyzer (DMA) while heating from 0°C at a heating rate of 5°C / min. The temperature at which tan δ reached its maximum value among the measured tan δ at each temperature was called the glass transition temperature, which is shown in Table 1 below. Since the first adhesive layer was formed from the same composition as the composition for the second adhesive layer, the first adhesive layer also had the glass transition temperature shown in Table 1 below.
[0141] [Table 1]
[0142] A: 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate (CELLOXIDE 2021P, Daicel Corporation) B: Resorcinol diglycidyl ether (EX-201, Nagase ChemteX Corporation) C: Phenyl glycidyl ether (EX-141, Nagase ChemteX Corporation) D: 4-Hydroxybutyl acrylate (Osaka Organic Chemical Industry Ltd.) E: Isodecyl acrylate (M-130, Miwon Specialty Chemical Co., Ltd.) F: Phenol (EO) acrylate (M-140, Miwon Specialty Chemical Co., Ltd.) G: Diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate (CPI-100P, San-Apro Co., Ltd.) H: 1-hydroxycyclohexyl phenyl ketone (IRGACURE 184, BASF) I: 3-Glycidoxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd.).
[0143] The polarizing plates manufactured in the Examples and Comparative Examples were evaluated for physical properties as shown in Table 2 below, and the results are shown in Table 2 below.
[0144] (1) Peel strength: The polarizing plates manufactured in the examples and comparative examples were left at 25°C for 2 minutes. Then, the polarizing plates were cut into width x length (25mm x 150mm) including the light-blocking portion (about 3cm), and a double-sided adhesive film was attached to the lower surface of the second liquid crystal retardation film, which was then fixed to a texture analyzer. After the light-blocking portion of the polarizing plate was spread, the first liquid crystal retardation film side was fixed to the jig of the texture analyzer. Then, this was left at 25°C for 72 hours. Then, the peel strength was measured when peeling the first liquid crystal retardation film and the second liquid crystal retardation film at a peel speed of 300mm / min and a peel angle of 90° at 25°C, and this was taken as the peel strength.
[0145] When the peeling force was less than 50 gf / 25 mm, it was indicated as x, when it was 50 gf / 25 mm or more and less than 100 gf / 25 mm, it was indicated as △, and when it was 100 gf / 25 mm or more, it was indicated as ◯.
[0146] (2) Reliability (unit: %): After producing the polarizing plate in the examples and comparative examples, a test piece was produced by cutting it to length x width (3 cm x 3 cm, MD of polarizer x TD of polarizer). The second liquid crystal retardation film of the produced test piece was made to face the light-emitting surface of V-7100 (JASCO Corporation), and the polarization degree of the polarizing plate was measured.
[0147] The initial polarization degree (P1) of the produced test specimen was measured by the method described above.
[0148] The prepared specimens were left in a heat-resistant chamber (constant temperature and high temperature at 85°C) or a humid heat-resistant chamber (constant temperature and humidity at 60°C and relative humidity of 95%, high temperature and high humidity) for 500 hours, respectively, and then the polarization degree (P2, P3) was measured by the method described above. The change in the polarization degree was calculated using Equation 1 and Equation 2.
[0149] (3) Flexibility: A 80 μm-thick polyethylene terephthalate (PET) film was adhered to one side of a polarizing plate with an acrylic adhesive, and a 80 μm-thick PET film was adhered to the other side of the polarizing plate with an acrylic adhesive. The polarizing plate was then cut to length x width (6 cm x 4 cm, length: MD of polarizer, width: TD of polarizer) to produce a test specimen consisting of PET film / polarizing plate / PET film.
[0150] According to IEC-62715, the test piece was mounted on a bending tester so that the PET film closest to the polarizer was on the inside when bent, and was bent at 25°C with a bending radius of 5 mm, a bending repetition rate of 30 times / min, and a bending angle of 180°. The first number of bends at which wrinkles or cracks occurred in the first liquid crystal retardation film and / or the second liquid crystal retardation film was obtained and evaluated according to the following criteria.
[0151] ○: 100,000 times or more △: 50,000 to less than 100,000 times X: Less than 50,000 times.
[0152] (4) Curability: In the manufacturing process of the polarizing plates of the examples and comparative examples, the joined parts were peeled off 24 hours after the light irradiation in (2). If the liquid crystal retardation film was easily separated, it was rated as ◯, and if the adhesive remained or came into contact with the hands in an uncured state, it was rated as X.
[0153] [Table 2]
[0154] As shown in Table 2 above, the polarizing plate for a light-emitting display device of the present invention had excellent peel strength from the liquid crystal retardation film, and was excellent in reliability and flexibility.
[0155] On the other hand, the polarizing plate of the comparative example in which the first adhesive layer and the second adhesive layer of the present invention were not formed was unable to obtain all the effects of the present invention.
[0156] Simple modifications and variations of the present invention can be easily implemented by those having ordinary skill in the art, and all such modifications and variations can be considered as falling within the scope of the present invention.
Claims
1. A polarizing plate for a light emitting display device, comprising: a polarizer; and a first adhesive layer, a first liquid crystal retardation film, a second adhesive layer, and a second liquid crystal retardation film, which are sequentially laminated on one surface of the polarizer, The polarizing plate for a light emitting display device has a polarization degree change amount (ΔPE 1 , △PE 2 ) are 0.7% or less, The first adhesive layer is formed of a composition for a first adhesive layer, the composition including an epoxy-based compound and a (meth)acrylate-based compound, The (meth)acrylate compound contained in the first adhesive layer composition includes a hydrophobic (meth)acrylate compound, The second adhesive layer is directly formed on the first liquid crystal retardation film and the second liquid crystal retardation film, respectively, and is formed of a composition for a second adhesive layer including an epoxy-based compound and a (meth)acrylate-based compound; The (meth)acrylate compound contained in the second adhesive layer composition includes a hydrophobic (meth)acrylate compound, The hydrophobic (meth)acrylate-based compound contained in the composition for the second adhesive layer includes a (meth)acrylate having a linear or branched unsubstituted alkyl group having 6 to 20 carbon atoms and a (meth)acrylate having an unsubstituted aromatic group. [0010] (In the above formula 1, a polarizing plate is cut to a length x width (3 cm x 3 cm, MD of polarizer x TD of polarizer), and the initial polarization degree measured for the test piece is P1 (unit: %), The polarization degree measured after leaving the test piece at a constant temperature of 85°C for 500 hours is called P2 (unit: %). [0025] (In the above formula 2, a polarizing plate is cut to a length x width (3 cm x 3 cm, MD of polarizer x TD of polarizer), and the initial polarization degree measured on the test piece is called P1 (unit: %), and the polarization degree measured after leaving the test piece at a constant temperature and humidity of 60°C and a relative humidity of 95% for 500 hours is called P3 (unit: %).)
2. 2. The polarizing plate for a light-emitting display device according to claim 1, wherein the (meth)acrylate having a straight-chain or branched-chain unsubstituted alkyl group having 6 to 20 carbon atoms includes at least one of isodecyl (meth)acrylate and decyl (meth)acrylate.
3. The polarizing plate for a light-emitting display device according to claim 1 , wherein the epoxy compound contained in the composition for the second adhesive layer comprises an alicyclic epoxy compound.
4. The polarizing plate for a light-emitting display device according to claim 3 , wherein the epoxy compound contained in the composition for the second adhesive layer further contains an aromatic group-containing glycidyl ether.
5. The polarizing plate for a light-emitting display device according to claim 4 , wherein the aromatic group-containing glycidyl ether comprises at least one of phenyl glycidyl ether and resorcinol diglycidyl ether.
6. The polarizing plate for a light-emitting display device according to claim 1 , wherein the composition for the second adhesive layer does not contain a (meth)acrylate-based compound having a hydrophilic group.
7. 2. The polarizing plate for a light-emitting display device according to claim 1, wherein the (meth)acrylate-based compound contained in the composition for the second adhesive layer is contained in an amount of 25 to 65 parts by weight per 100 parts by weight of the total of the epoxy-based compound and the (meth)acrylate-based compound contained in the composition for the second adhesive layer.
8. The polarizing plate of claim 1 , wherein the composition for the second adhesive layer further comprises a photocationic initiator and a photoradical initiator.
9. The second adhesive layer composition is 35 to 90 parts by weight of the epoxy compound, 10 to 65 parts by weight of the (meth)acrylate compound, For a total of 100 parts by weight of the epoxy compound and the (meth)acrylate compound, 1 part to 10 parts by weight of the photocationic initiator, The polarizing plate for a light emitting display device according to claim 8 , comprising 0.5 to 10 parts by weight of the photoradical initiator.
10. The polarizing plate for a light emitting display device according to claim 1 , wherein the second adhesive layer has a glass transition temperature of 70° C. to 110° C.
11. The polarizing plate for a light-emitting display device according to claim 1 , wherein the composition for the first adhesive layer does not contain a (meth)acrylate-based compound having a hydrophilic group.
12. The polarizing plate for a light emitting display device according to claim 1 , wherein the first adhesive layer has a glass transition temperature of 70° C. to 110° C.
13. 2. The polarizing plate for a light-emitting display device according to claim 1, wherein the first liquid crystal retardation film and the second liquid crystal retardation film are each formed of a composition containing at least one of an alicyclic group-containing (meth)acrylic liquid crystal compound and an aromatic group-containing (meth)acrylic liquid crystal compound.
14. The polarizing plate for a light emitting display device according to claim 1 , further comprising a protective layer formed on another surface of the polarizer.
15. A light-emitting display device comprising the polarizing plate for a light-emitting display device according to claim 1 .
16. The light emitting display device of claim 15 , wherein the light emitting display device comprises a foldable light emitting display device.
Citation Information
Patent Citations
Manufacturing method for laminate
JP2015079230A
Optical film, manufacturing method thereof, and display device
JP2016012134A
Optical film, polarizing plate, and image display device
JP2017111212A
Adhesive composition for polarizing plate, polarizing plate and optical display apparatus
KR1020190082624A
Polarizing plate provided with adhesive, and liquid crystal display device
WO2015182351A1